Healthcare Workplace Hazards: A Multilingual Assessment of Nursing, Pharmacy, Optics, Social Sciences, and Epidemiology - Al Sharif, Naif Ahmed; Kabi, Khalid Mohammed Hassan; Alshayeb, Haithem Ahmed Abdulmajeed; Asiri, Abdullah Omar Hifthi; Asiri, Jaber Ali Hamad; Alzaid, Essam Daifallh Ibrahim; Muqarbish, Mohammed Abdu Hamad; Safhi, Khaled Ahmed Gasem; AlDossary, Madiha Rashid; Al-Qahtani, Khalid Abdullah Mohammed; Alresheedi, Ayad Salem Suwailem; Alharbi, Sufyan Abbas Abdullah (Journal of Ecohumanism, 2024)
Healthcare professionals across various disciplines face a broad spectrum of occupational hazards that can significantly impact their physical, mental, and emotional well-being. These hazards differ based on specific work environments, job responsibilities, and levels of exposure to biological, chemical, ergonomic, and psychosocial risks. Nursing professionals are particularly vulnerable to infectious diseases, needlestick injuries, and musculoskeletal disorders due to the physical demands of patient care. Pharmacists, on the other hand, face risks associated with prolonged exposure to hazardous drugs and chemicals. In the field of optics, ergonomic strain from repetitive tasks and prolonged screen exposure can lead to musculoskeletal issues and visual fatigue. Social scientists conducting healthcare research frequently experience psychological stress and burnout, especially when addressing sensitive public health issues. Epidemiologists, particularly those involved in infectious disease surveillance and outbreak response, are exposed to biological hazards and mental strain due to the high-stakes nature of their work. This review provides a comprehensive multilingual assessment of workplace hazards across these five healthcare-related disciplines. By drawing on research published in different languages, we aim to present a global perspective on occupational risks and safety practices. This interdisciplinary approach highlights the importance of international collaboration in developing effective workplace safety policies and preventive measures. Key strategies for mitigating these hazards include ergonomic interventions, improved infection control measures, mental health support programs, and regulatory frameworks to protect healthcare workers. Understanding these diverse workplace challenges is crucial for improving occupational health standards and fostering a safer working environment for healthcare professionals worldwide.